Correlation Between Altmetric Score and Traditional Bibliometrics in Total Joint Arthroplasty Research - Pradip Ramamurti, BS; Alex Gu, MD; Safa C. Fassihi, MD; Seth Stake, MD; Chapman Wei, BS; Joshua Campbell, MD; Savyasachi Thakkar, MD (Arthroplasty Today, 2021)
Background: Citation analysis is commonly used to evaluate the impact of academic publications within an area of study. The purpose of this study is to review the publications with the highest Altmetric scores related to total hip arthroplasty (THA) and total knee arthroplasty (TKA) and assess the correlation with traditional bibliometrics. Methods: Altmetric scores were obtained for the top articles relating to THA and TKA and organized from highest to lowest scores. The Clarivate Analytics Web of Knowledge database was used to search the top articles by Altmetric score. Articles meeting inclusion criteria were reviewed for various metrics, including number of citations, journal impact factor at the time of publication, and study type and design. Results: The top THA and TKA publications were cited 3042 times and 7523 times, respectively. The former were published in journals with an average impact factor of 17.861, and the latter in journals with an average impact factor of 15.564. For THA, Altmetric score demonstrated a significant, weakly positive correlation with the number of citations (P = .008). For TKA, Altmetric score was found to have a significant, weakly positive correlation with impact factor of journal (P = .04); however, it was nonsignificant for citation count (P = .11). When one outlier is removed, the correlation with citation count is statistically significant (P = .009). Conclusion: While alternative metrics cannot replace traditional bibliometrics, they may serve a complimentary role in describing the influence of research. Thus, the Altmetric score represents an additional tool to identify the most influential articles to guide learning and evidence-based practice.